Panglima Laot Aceh in Maritime System Since 2000-2024 - Rahmah, Sri; Yulifar, Leli (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This research aims to understand the origins of the Panglima Laot Aceh, as well as the duties and functions of the Panglima Laot Aceh in the Aceh Maritime Affairs from 2000-2024. The study utilizes historical methods, with data collection through interviews, documentation, and literature review. Primary sources include documents and interviews with Panglima Laot Aceh, Teungku Miftach Tjut Adek, while secondary sources include books, journals, theses, news, and internet sites. The position of Panglima Laot has existed since the Samudra Pasai Kingdom in the 14th century, and during Sultan Iskandar Muda's reign (1607-1636), the role of Panglima Laot became clearer. During the colonial era, the Panglima Laot served as the leader of a group of fishermen who resolved disputes among them. After independence, in the year 2000, the Panglima Laot of Lhok held a meeting in Banda Aceh, resulting in the formation of a provincial-level Panglima Laot in Aceh. During the kingdom period, the Panglima Laot's duties included collecting taxes and mobilizing the masses for warfare on behalf of the sultan. Nowadays, the Panglima Laot is responsible for managing marine and fisheries affairs, especially overseeing fishing activities in the Aceh sea, as well as regulating the actions of Acehnese fishermen.